2017
DOI: 10.1038/s41598-017-11689-w
|View full text |Cite
|
Sign up to set email alerts
|

Propolis envelope in Apis mellifera colonies supports honey bees against the pathogen, Paenibacillus larvae

Abstract: Honey bees have immune defenses both as individuals and as a colony (e.g., individual and social immunity). One form of honey bee social immunity is the collection of antimicrobial plant resins and the deposition of the resins as a propolis envelope within the nest. In this study, we tested the effects of the propolis envelope as a natural defense against Paenibacillus larvae, the causative agent of American foulbrood (AFB) disease. Using colonies with and without a propolis envelope, we quantified: 1) the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 48 publications
0
19
0
1
Order By: Relevance
“…This observation begs the question of why highly hygienic colonies are rare in nature and whether there are associated fitness costs with the trait (Spivak and Gilliam 1993;Mondragon et al 2005;Bigio et al 2014;Leclercq et al 2017). We speculate that resistance does not depend solely on hygienic behavior but likely involves a combination of other physiological factors in honey bees, including the immune response (Evans and Spivak 2010), transgenerational immune priming (Hernandez Lopez et al 2014), microbiome community (Raymann and Moran 2018), antimicrobial activity of larval food (Rose and Briggs 1969;Borba and Spivak 2017), presence of propolis in the nest (Borba et al 2015), and other factors yet to be discovered.…”
Section: A S S a Y S F O R H O N E Y B E E Hygienic Behaviormentioning
confidence: 91%
“…This observation begs the question of why highly hygienic colonies are rare in nature and whether there are associated fitness costs with the trait (Spivak and Gilliam 1993;Mondragon et al 2005;Bigio et al 2014;Leclercq et al 2017). We speculate that resistance does not depend solely on hygienic behavior but likely involves a combination of other physiological factors in honey bees, including the immune response (Evans and Spivak 2010), transgenerational immune priming (Hernandez Lopez et al 2014), microbiome community (Raymann and Moran 2018), antimicrobial activity of larval food (Rose and Briggs 1969;Borba and Spivak 2017), presence of propolis in the nest (Borba et al 2015), and other factors yet to be discovered.…”
Section: A S S a Y S F O R H O N E Y B E E Hygienic Behaviormentioning
confidence: 91%
“…Previous research has established the benefits of a propolis envelope for colony health and disease resistance. Propolis in the colony is correlated or associated with increases in colony strength, vitellogenin levels, the antimicrobial activity of larval food, adult bee longevity, brood survival rates, hygienic behavior, and honey production [ 6 , 7 , 8 , 9 , 10 , 11 ]. Additionally, a reduction in deformed wing virus titers was found in colonies with propolis (even though Varroa destructor mite infestation did not change [ 12 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a reduction in deformed wing virus titers was found in colonies with propolis (even though Varroa destructor mite infestation did not change [ 12 ]). After an experimental pathogen challenge, colonies with a propolis envelope had fewer clinical signs of chalkbrood [ 2 ] and American foulbrood [ 7 ] compared to colonies without a propolis envelope. Simone et al [ 3 ] and Borba et al [ 6 ] found that colonies with a propolis envelope exhibited a reduced investment in individual bee immune function.…”
Section: Introductionmentioning
confidence: 99%
“…Bees that collected larger quantities of propolis were reported to be healthier, producing viable broods and displaying superior hygienic behavior compared with the ones that collected less [76,77,81]. It was also found that bees usually respond to pathogens by collecting more propolis to ward off infections, while the immunity of the colony against infection is improved by the propolis envelop [78,82,83]. In addition, the microbiome of the bee colony is stabilized by propolis [84].…”
Section: Evidence For Propolis Protection Against Bee Infectionsmentioning
confidence: 99%